278 DETERMINANTS OF ELEVATED FILLING PRESSURE IN ADVANCED SYSTOLIC HEART FAILURE. Issue 1 (1st January 2007) - Sadhu, A.; Simoni, J.; Simoni, G.; Moeller, J.; Pierce, M.; Roongsritong, C.
Abstract : Purpose of Study: Elevated filling pressure has been associated with worse outcome in patients with systolic heart failure. Determining factors of elevated filling pressure in these patients have not been well described. The ratio of early filling (E wave) on transmitral Doppler inflow to early diastolic velocity of mitral annulus (E') has been shown to be an accurate predictor of elevated filling pressure. We sought to identify echocardiographic and/or clinical variables that correlate with E/E' > 15. Methods Used: Forty patients with systolic heart failure (EF < 35%) and an adequate echocardiographic study for the evaluation of E/E' within 3 months were enrolled. The subjects were then divided into those with E/E' ≤ 15 (group I) and E/E' > 15 (group II). Serum carboxy-terminal of procollagen type I (PICP) levels were measured using a commercially available ELISA kit (Takara Inc.). Data are presented as mean ± standard deviation. Clinical and echocardiographic data are compared between the two groups using Student's t -test or chi-square test when appropriate; p values < .05 are considered statistically significant. Summary of Results: There were no significant differences in age, gender, race, serum creatinine, and etiology of heart failure between the two groups (Table ). Conclusions: In this pilot study, serum marker of myocardial fibrosis (PICP) and left atrial size, among the variable tests, were the only predictors of elevated filling pressure in our patients with advanced systolic heart failure. Further investigation in a larger population on the role of fibrotic marker for identifying patients with elevated filling pressure may be warranted.